STABILITAS ANTOSIANIN DARI KULIT TERONG BELANDA MERAH (Solanum betaceum Cav.) TERHADAP PH DAN SUHU - Sandra Tri Juli Fendri; Verawati Verawati; Putri Saimi Nuras (Jurnal Katalisator, 2020)
There had been identification and stability test of anthocyanin liquid extract from skin of eggplant of Holland that red colored using UV-Vis spectrophotometer. Anthocyanin is a color compound that responsible mostly red, blue and purple in fruit, vegetables and ornamental plants and these anthocyanins belong to the flavonoid group. Eggplans of Holland is taken from Tabing market, Padang City. The extraction process was performed by maceration method using solvent of 96% ethanol: HCl 1% (9:1). The identification of the anthocyanin compound on the sample extract was done by color reaction with 2 M NaOH and 2 M HCl. Stability of the anthocyanin pigment was tested by both the pH and temperature difference treatments. The pH used was pH 1, 3, 5, 7 and 9, while the temperature used was 30oC, 40oC, 60oC, 80oC and 100oC. The parameters of stability are the color of solution, maximum wavelength (Î»max) and absorbance. The anthocyanin pigments stability test Eggplant of Holland was performed by using one-way of statistical data of variances (ANOVA), the liquid leather extract was stated stable at the influence of pH to temperature (temperature 30, 40, 60 and 80oC), especially at pH 1-3 next pH 5 and pH 7.Keywords : Anthocyanin, identification, pH, temperature, stability test